Carbon and oxygen isotope composition of carbonate in bulk sediment in the southwest Taiwan Basin, South China Sea: Methane hydrate decomposition history and its link to mud volcano eruption. (December 2018) - Zhang, Jie; Lei, Huaiyan; Chen, Yong; Kong, Yuan; Kandasamy, Selvaraj; Ou, Wenjia; Cheng, Weidong
Abstract: Anaerobic oxidation of methane (AOM) coupled with sulfate reduction (SR) generates authigenic carbonate which has the unique carbon and oxygen isotope composition in sulfate methane transition zone (SMTZ). The carbon and oxygen isotope composition of carbonate in sediments, which can be used to revel the variable methane flux, is affected by the percentage of AOM-driven carbonate in sediments. To investigate the methane hydrate decomposition history in the southwest Taiwan Basin, we analyzed a 13 m-long sediment core for grain size, carbonate and elemental carbon contents and stable carbon and oxygen isotopes composition of carbonate (δ 13 Ccarb and δ 18 Ocarb ). The AMS 14 C dating results and carbonate content reveal that a turbidity current occurred at around 14 ka B.P., which reversed sediment accumulation between 455 and 885 cm in depth. Combining the chronological framework and δ 13 Ccarb values, we identified that the methane hydrate decomposition scale began to decrease at 14 ka B.P. Moreover, we discovered that three transiently enhanced methane hydrate decomposition events occurred from then on. Although the δ 13 Ccarb and δ 18 Ocarb variability are as expected, the low δ 18 Ocarb values are inconsistent with the previous theory which favors 18 O-enriched in AOM-driven authigenic carbonate. Thus, we suggest that a large amount of 18 O-depleted water which originally migrated from southwest Taiwan island was injected into surface sediment along with the eruption of mud volcanos. As the terminal electron accepter of AOM-SR reaction, the exogenous 18 O-depleted water leads its special oxygen isotope to be inherited by the authigenic AOM-driven carbonate. The proposed theory provides new insights on the authigenic carbonate in methane hydrate area and the association between methane hydrates and mud volcanoes. Highlights: At least three enhanced methane hydrate decomposition events occurred during last 14 ka. Methane hydrate decomposition associated with the mud volcano eruption in study area. Mud volcano eruption injected large amount of 18 O-depleted water into surface sediment. The 18 O-depleted water may come from Taiwan Island, as submarine groundwater discharge.